2006
DOI: 10.1017/s0950268806007333
|View full text |Cite
|
Sign up to set email alerts
|

Using facsimile cascade to assist case searching during a Q fever outbreak

Abstract: In September 2002, facsimiles were sent to 360 primary-care physicians alerting them to a local outbreak of Q fever. The physicians subsequently submitted serology samples on significantly more patients than in a previously comparable period in 2001. Facsimile cascade assists effective communication with primary-care physicians in an outbreak investigation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2011
2011
2011
2011

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Eleven articles (covering 9 systems) included a description of the evaluation used with the system. Type of evaluations included comparative [ 19 ], interviewing [ 20 ], surveying [ 21 , 22 ], retrospective [ 23 , 24 ], formative [ 25 ], and an assessment following a simulation exercise [ 26 ]. One article reported a causal relationship could be "inferred" between the dissemination of health advisories and HCP reporting and testing [ 27 ] and two reported receiving feedback but did not detail method [ 28 , 29 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Eleven articles (covering 9 systems) included a description of the evaluation used with the system. Type of evaluations included comparative [ 19 ], interviewing [ 20 ], surveying [ 21 , 22 ], retrospective [ 23 , 24 ], formative [ 25 ], and an assessment following a simulation exercise [ 26 ]. One article reported a causal relationship could be "inferred" between the dissemination of health advisories and HCP reporting and testing [ 27 ] and two reported receiving feedback but did not detail method [ 28 , 29 ].…”
Section: Resultsmentioning
confidence: 99%
“…During a Q fever outbreak, two public health alert faxes were sent asking physicians to submit serum samples on any patient meeting a clinical case definition of Q fever and an association with the area where the outbreak occurred. By examining laboratory reports, Van Woerden et al (2006) found a statistically significant difference between the number of patients tested for Q fever in the target population after the alerts had been sent as compared to a comparable two-week period one year before [19].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation